Community Structure of Zooplanktonic Groups of Chimdi Lake, Sunsari, Nepal (Our Nature, 2006)
Community structure of zooplankton in Chimdi Lake was assessed during the year 2003-2005. During the period of investigation 15 species of zooplanktons representing 3 groups namely Rotifera, Copepoda and Cladocera were recorded. Key words: Birju Tal, Chimdi Lake, Zooplanktondoi:10.3126/on.v3i1.339Our Nature (2005) 3: 81-82